Pengembangan Handout Biologi Berbasis Discovery Learning pada Materi Interaksi Mahluk Hidup dengan Lingkungannya - Wahyu Nur Susanto; Supiana Dian Nurtjahyani (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2018)
In the background exposure obtained at the observation stage shows the need for the development of other learning media that can improve students' motivation and interest to the need for development of discovery learning biology handdout on the material interaction of living creatures with the environment, this development aims to develop a learning media in the form of handout based on discovery learning that is interesting and can motivate students in learning and know the level of feasibility (valid, effective and practical) development as a biology learning media on the material interaction of living creatures with the environment in SMP Muhammadiah 2 Palang.Penelitian this is the type of research development or Research and Development (R & D) with development method using ADDIE model. This model has 5 stages: analysis, design, development of trial and evaluation. To test the feasibility of validation. Product validation is done by lecturers of material experts and instructional media to get input and suggestions on the feasibility of handouts in terms of material or media. And the results showed that the feasibility level of discovery learning biology based handout is declared valid, practical and effective